YAP Transcriptional Activity Dictates Cell Response to TNF In Vitro - Caire, Robin; Dalix, Elisa; Chafchafi, Marwa; Thomas, Mireille; Linossier, Marie-Thérèse; Normand, Myriam; Guignandon, Alain; Vico, Laurence; Marotte, Hubert (Frontiers in Immunology, 2022)
YAP/TAZ are transcription co-factors recently described responsive to pro-inflammatory cytokines and involved in inflammatory-related disorders. However, the role of tumor necrosis factor (TNF), a major pro-inflammatory cytokine, on YAP signaling is not well understood and controversial. Here, we observe in vitro, using wild type and YAP knockout HEK293 cells, that TNF triggers YAP nuclear translocation and transcriptional activity, thus being dependent on Rho family of GTPases. In response to TNF, YAP transcriptional activity orientates cell fate toward survival. Transcriptional analysis with Nanostring technology reveals that YAP modulates TNF-induced increase in fibro-inflammatory pathways such as NF-κB, inflammasomes, cytokines or chemokines signaling and pro-fibrotic pathways involving TGF-β and extracellular matrix remodeling. Therefore, in response to TNF, YAP acts as a sustainer of the inflammatory response and as a molecular link between inflammation and fibrotic processes. This work identifies that YAP is critical to drive several biological effects of TNF which are involved in cancer and inflammatory disorders.